KESADARAN SAAT MAKAN DAN HUBUNGANNYA DENGAN KESEHATAN HOLISTIK DI ERA MODERN - Kasingku, Juwinner; Winda Novita Warouw (Nusantara Hasana Journal, 2026)
Human health includes physical, mental, and spiritual well-being, all of which are closely connected. In today’s modern era, many people consume fast food and processed foods that are high in sugar, fat, and salt. These habits increase the risk of diseases such as obesity, type 2 diabetes, and heart disease. This study aims to examine the importance of a healthy diet for human health based on scientific research and the writings of the Spirit of Prophecy. The method used is a literature review by collecting and analyzing relevant books and academic journals related to this topic. The findings show that a simple and natural diet, rich in plant-based foods such as fruits, vegetables, whole grains, and nuts, helps maintain physical health, strengthen the immune system, and support mental clarity and emotional stability. In contrast, overeating and irregular eating habits can disrupt the body’s metabolism, reduce concentration, and affect mood. The Spirit of Prophecy also emphasizes that the human body is the temple of the Holy Spirit and should be cared for responsibly. Therefore, self-control in food choices is important not only for physical health but also for character development and spiritual growth. By gradually and consistently applying healthy eating habits such as planning meals and reducing processed foods, individuals can achieve a healthier, more balanced life that is in harmony with God’s will.